Long QT syndrome is associated with an increased burden of diabetes, psychiatric and neurological comorbidities: a nationwide cohort study. Issue 2 (28th October 2019) - Marstrand, Peter; Theilade, Juliane; Andersson, Charlotte; Bundgaard, Henning; Weeke, Peter E; Tfelt-Hansen, Jacob; Jespersen, Camilla; Gislason, Gunnar; Torp-Pedersen, Christian; Kanters, Jørgen K; Jørgensen, Mads E
Abstract : Objective: Studies have suggested a shared genetic aetiology between congenital long QT syndrome (LQTS) and diabetes, epilepsy and mental disorders. We investigated the prevalence of metabolic, neurological and psychiatric comorbidities in LQTS patients. Methods: This retrospective cohort study was based on data from nationwide Danish registries, 2003–2017. LQTS patients were matched 1:5 with controls on sex and age. Results: We matched 463 LQTS patients with 2315 controls from the background population. Mean age was 35.7 (SD 21.0) years, and 38% were males in both groups. LQTS patients had a higher prevalence of atrial fibrillation (6.5% vs 2.3%, p<0.001), diabetes (3.7% vs 1.8 %, p=0.011) and hearing loss (3.2% vs 1.7%, p=0.027). LQTS patients had a higher prevalence of psychiatric disorders overall (13.0% vs 9.1%, p=0.01) but the difference could not be attributed to a specific psychiatric disease subgroup. LQTS patients had a higher prevalence of neurological disorders (22.0% vs 13.2%, p<0.001), largely driven by epilepsy (6.7% vs 1.6%, p<0.001). In 20/27 (74%) of the LQTS patients, the epilepsy diagnosis did not reappear in the registries after the LQTS diagnosis was established. Conclusions: In this nationwide cohort, patients with LQTS had a significantly increased burden of diabetes, neurological and psychiatric comorbidities, compared with the background population. The higher prevalence of neurological comorbidities was largely driven by epilepsy, despite a high rate of potentially misdiagnosed patients prior to LQTS diagnosis. Our data support that LQTS may be considered a multiorgan disease and suggest that patient management should be adjusted accordingly.